Probiotic properties of lactobacilli isolated from Thai traditional food - Srikanjana Klayraung (2018)
Certain properties relevant to probiotic action, e.g. resistance to acid, bile tolerance, adhesive properties, antibacterial activity, and antibiotic susceptibility were investigated of lactobacilli isolated from four kinds of Thai traditional fermented foods. Media of pH = 2.0-7.0 and bile salt concentrations of 0.3-1.0% were used as stress conditions. The adhesive properties were assessed by determination of bacterial hydrophobicity. Antibacterial activity of the probiotic lactobacilli was determined by means of the spot-on-lawn method. Among 563 isolates, only 3 strains (two from fermented pork and one from fermented tea leaves) showed extremely high survival rates under stress caused by acid or bile salts. The identification by PCR techniques revealed that these three strains were Lactobacillus fermentum. The strains from fermented pork showed higher adhesive potential than those from fermented tea leaves. The three strains inhibited test pathogenic bacteria to different extents. They were sensitive to chloramphenicol, quinupristin, erythromycin, kanamycin linezolid, rifampicin, streptomycin, and tetracycline but resistant to ciprofloxacin and vancomycin. © Osterrechische Apotheker- Verlagsgedellschaft m.b.H.